Synthesis and Pharmacological Evaluation of Novel Quinazoline Derivatives as Potential EGFR Inhibitors for Breast Cancer - Dwivedi, Deepak K.; Agrawal, Ram Kishore (International Journal of Pharmaceutical Investigation)
Background: Breast cancer is the highest mortality-causing disease among cancers in women and it can be cured by early diagnosis as well as treatment. Epidermal growth factor receptor-2 (HER2) is the prime factor that helps in the growth and development of breast cancer. There are several EGFR inhibitors approved for breast cancer treatment, but all are shown to cause resistance and severe toxicity. The present research work is based on the synthesis and pharmacological evaluation of novel derivatives against breast cancer cell lines. Materials and Methods: Ten novel Quinazoline derivatives (4a-j) were synthesized and characterized by IR, PMR, and CMR spectroscopic methods. Cell proliferation and cytotoxic effects of synthesized derivatives were determined by using MTT assay and hemolytic assay. Results: The growth inhibition potential of synthesized derivatives was evaluated against normal as well as mutated breast cancer cell lines i.e., MCF-7 and MDA-MB-231 using the MTT method. Nearly, five derivatives 4b, 4c, 4e, 4f, 4i for MCF-7 and 4b, 4c, 4d, 4e, 4f, 4i for MDA-MB231 were assessed for IC50 value. It was observed that these compounds of the series exhibited higher IC50 values (8.72 to 15.70, 12.66 to 21.21µM/mL) as compared to erlotinib with IC50 values (16.80, 22.80), respectively. Moreover, the hemolytic estimation of the derivatives (4e, 2-Br) and (4i 4-CN) displayed less toxicity with HD50 values 69.87±8.9, 58.40±3.2, respectively. Conclusion: The findings of the current study provide safe, less-toxic, cost-effective, and potent novel quinazoline derivatives for breast cancer.
Keywords: 5-nitroanthranilic acid; Anilines; Anti-cancer activity; Breast cancer; Hemolytic activity.